Does a higher training age attenuate injury risk in junior elite rugby league players? - Booth, M.; Cobley, S.; Orr, R. (International Journal of Sports Science & Coaching, 2019)
Our aim was to determine the relationships between three different training ages - TA domains (Rugby League specific - RLTA; Resistance training - RTA; Cardiovascular training - CVTA) on injury risk in junior elite rugby league players. Participants were 147 developmental rugby league players (mean age = 15.8 ± 1.1 years) playing for one rugby league club. Logistic regression with RLTA, CVTA and RTA as independent predictors was modelled on injured/uninjured outcomes. Relationships between TA and injury characteristics were examined using linear regression. CVTA was positively associated with absolute injury risk (odds ratio - OR 1.65, p = 0.02) and injury characteristics (muscle strain OR 1.12, p = 0.05) and ankle injuries (OR 1.24, p = 0.05). A positive association was demonstrated between RTA and high-intensity running injuries (OR 1.31, p = 0.01), and hamstring injuries (OR 1.66, p = 0.01). Our results suggest that a higher pre-study CVTA and RTA was associated with increased injury risk in an elite development rugby league team.